El Excentrico, 1973-01-05 - Garcia, Humberto:::Publisher:::::::::::: (San Jose, California; Garcia Printing, 2023)
January 5, 1973 [5 de enero de 1973]. No volume or issue number. Cover has an advertisement for Arturo's Quiet Village, a live entertainment venue, with a photograph of a man on a stage that has been decorated for the holidays.